(3GdLGeY GdUZjQs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdUdGI s
(3BNQgG (B:s
(3jfJgi HeSGFd eJaQbI djS dgG CHhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs